Employment law for human resource practice - Walsh, David J. (Cengage Learning, 2024)
Packed with cutting-edge cases and hands-on applications, Walsh's Employment law for human resource practice, 7E explains major issues and rules of employment law behind each step of the employment process -- all in understandable terms. You learn how law impacts your career, as a manager or employee. Current news, typical situations and real cases help you understand how legal concepts apply to each stage of employment -- from hiring and managing to firing. Each chapter begins with new learning objectives and ends with a summary of practical advice for today's managers. Updates addresses the latest topics in employment law, from discrimination based on sexual orientation and ""gig workers"" to COVID-19, pay equity and other pressing issues. This edition provides insights to help you prevent discrimination and harassment, accommodate employees with disabilities, comply with wage and hour laws, and avoid wrongful terminations and other common legal issues.